Rhinolekos, a new genus with three new species of Hypoptopomatinae (Siluriformes: Loricariidae) from upper rio Paraná - Martins,Fernanda de Oliveira (2011)
Rhinolekos, new genus, and three new species, R. britskii, R. garavelloi, and R. schaeferi, are described from rio Paranaíba, upper rio Paraná drainage, central Brazil. Rhinolekos can be diagnosed by the following combination of characters: anterior portion of the compound supraneural-first dorsal-fin proximal radial contacting the neural spine of the 9th or 10th vertebrae; presence of the lateronasal plate; absence of the median rostral plate; presence of the pectoral-fin axillary slit just in juvenile specimens; ventral surface of pectoral girdle exposed only laterally; arrector fossae partially enclosed, with opening relatively large, extending laterally halfway towards pectoral-fin base; paired anterior process of the compound supraneural-first dorsalfin proximal radial bone absent; median plate series continuous to the caudal-fin origin; iris operculum present; pteroticsupracleithrum quadrangular in shape and not extending posteriorly; supraoccipital not contributing to the dorsal portion of the swimbladder capsule; subopercular plate present; dorsal and ventral margins of snout bearing odontodes roughly equivalent in size and shape to those on remainder of the head; caudal peduncle roughly rounded in cross section; longitudinal crests in supraoccipital absent; fourth infraorbital expanded ventrally.